Muon tomography with Micromegas: Archaeology, nuclear safety and new developments for Geotechnics. (September 2019) - Gómez, H.; Attié, D.; Calvet, D.; Coppolani, X.; Gallois, B.; Kebbiri, M.; Lehuraux, M.; Magnier, P.; Mandjavidze, I.; Procureur, S.; Vandenbroucke, M.
Abstract: Muon tomography, or muography, stands out as a non-invasive technique for the scanning of big objects' internal structure. It relies on the measurement of the direction changes or absorption of atmospheric muons when crossing the studied object. Proposed several decades ago, the performance achieved in particle detectors in the last years, specially in terms of stability, robustness and precision, has enlarged the possible applications of this technique. Bulk Micromegas represent a well-known technology suitable for the construction of muon telescopes based on these detectors. Thus autonomous and portable instruments have been conceived and constructed at Commissariat à l'Énergie Atomique et aux Énergies Alternatives (CEA), being able to perform muography measurements in-situ, next to the studied objects. At present, a new muon telescope concept is being developed at CEA, combining a Time Projection Chamber (TPC) readout by a 2D multiplexed bulk Micromegas. This new generation of detectors will enlarge the possible application fields of muography, being specially interesting for geotechnics.